Adding value to livestock diversity :marketing to promote local breeds and improve livelihoods / (Acc: D 388) marketing to promote local breeds and improve livelihoods - Mathias, Evelyn; Mundy, Paul. (Rome : League for Pastoral Peoples and Endogenous Livestock Development : LIFE Network : International Union for Conservation of Nature : Food and Agriculture Organization of the United Nations, 2010)
"Many local livestock breeds and minor species are in decline and may be lost because they cannot compete with high-yielding exotic breeds. Conserving these breeds is important: many have unique traits, such as hardiness and disease resistance, that are vital for future livestock production. One way to help ensure their survival may be to sell products from these breeds to high-value, specialist markets. The Global Plan of Action for Animal Genetic Resources acknowledges the importance of market access to the sustainable use of livestock diversity and calls for development of markets for products derived from local species and breeds, and for strengthening processes that add value to their products. This publication describes eight examples of marketing of livestock products (wool, cashmere, milk, meat and hides) from local breeds of Bactrian camels, dromedaries, goats and sheep in seven countries in Africa, Asia and Latin America. It shows how they have kept local breeds in use, while enabling the small-scale livestock keepers and pastoralists who raise them to improve their livelihoods"--P. [4] of cover.
Keywords: Animal products; Livestock diversification; Wool; Meat; Milk